RANCANG BANGUN SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN SISWA BERPRESTASI BERBASIS SIMPLE ADDITIVE WEIGHTING - Prasetyo, Muhammad Dody; Amrizal, Amrizal (Computer Science and Industrial Engineering, 2023)
The selection of outstanding students at MIS Imadun Ghoffar went through a long and complicated process. The selection process has the opportunity to make wrong decisions in the selection process, because the student selection process is based on subjectivity, which means that the selected outstanding students will most likely not reach the desired level and will not get the best candidate. Therefore, a decision support system is created that can calculate all the criteria for selecting outstanding students. In this work, the SAW (Simple Additive Weighting) method is implemented. This method makes decision making easier. The problem to be solved is divided into several elements, namely Criteria. The criteria needed are the average value of report cards, extracurricular scores, attitude scores and absences. The results of this system are expected to produce outstanding students according to the specified criteria. From this it can be concluded that the decision support system for selecting outstanding students at MI Imadun Ghoffar can be a solution or consideration in selecting outstanding students.